An ADDIE-Based Educational Arithmetic Game for Children with Mild Intellectual Disabilities - Wenda Novayani; Shumaya Resty Ramadhani; Eveline Ang (Journal of Information System and Informatics, 2026)
This study presents the design and evaluation of BRILIAN, an educational arithmetic game developed to support children with mild intellectual disabilities using the ADDIE instructional design framework. The study addresses persistent challenges in numeracy learning-particularly addition and subtraction-where conventional instructional approaches often fail to sustain learner engagement and instructional effectiveness. A mixed-methods approach was employed across the ADDIE phases, incorporating teacher interviews, functional testing, standardized usability and user experience instruments (System Usability Scale, User Experience Questionnaire-Short, and Game User Experience Satisfaction Scale), classroom observations, and pre-test/post-test performance assessments. The findings indicate high usability and user satisfaction, with a mean SUS score of 75.20 and an overall GUESS score of 87.74%. Teacher observations further revealed strong learner engagement (90.26%). Learning effectiveness improved significantly, as reflected by an increase in mean test scores from 62.73 to 82.27, accompanied by reduced task completion time. By integrating structured instructional design, multimodal feedback, adaptive gameplay, and cognitive accessibility features, this study provides empirical evidence that ADDIE-based educational games can function as practical and effective instructional tools for arithmetic learning in special education classroom contexts.